2018
DOI: 10.1192/bjo.2017.11
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, factors and reasons associated with missed first appointments among out-patients with schizophrenia at the Federal Neuro-Psychiatric Hospital, Benin City

Abstract: BackgroundNon-attendance to clinic appointments is associated with poorer treatment outcomes. There is a dearth of information about missed first clinic appointments among patients with schizophrenia in Nigeria.AimsTo determine the prevalence, correlates and reasons for missed first appointment among out-patients with schizophrenia at the Federal Neuro-Psychiatric Hospital, Benin City, Nigeria.MethodA cross-sectional descriptive study among 275 out-patients with schizophrenia, using the Mini International Neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…We found that 22.9% of patients did not attend the consultation appointment. This was consistent with the attendance rate found in a study of missed first appointments among youth and adults with schizophrenia . This finding, along with evidence that approximately one-third of patients with early psychosis disengage from services prematurely, suggests that patients face engagement challenges throughout their service trajectories.…”
Section: Discussionsupporting
confidence: 86%
“…We found that 22.9% of patients did not attend the consultation appointment. This was consistent with the attendance rate found in a study of missed first appointments among youth and adults with schizophrenia . This finding, along with evidence that approximately one-third of patients with early psychosis disengage from services prematurely, suggests that patients face engagement challenges throughout their service trajectories.…”
Section: Discussionsupporting
confidence: 86%
“…Given the rarity of this pathology, research regarding the relationship between schizophrenia and DFSP has not been conducted, however, a large meta-analysis found that patients with psychotic disorders had a higher incidence of testicular cancer (relative risk 1.27) and 22% higher odds of metastasis at diagnosis compared to those without psychotic disorders [ 15 ]. Additionally, patients with schizophrenia had high rates of appointment non-adherence, with the prevalence of a missed first appointment after hospitalization being over 30% [ 16 - 17 ]. This patient is now three months from surgery and unfortunately has not presented to follow-up appointments despite multiple attempts to reach the patient and family members.…”
Section: Discussionmentioning
confidence: 99%
“…However, poor initial adherence remains a global challenge for psychiatric practices [ 3 , 21 ]. Ibironke et al reported a prevalence of 30% of missed first appointments 2–3 weeks after the first outpatient visit in patients with schizophrenia [ 8 ]. According to National Comorbidity Survey Replication data, the mental health treatment dropout rate from the general medication sector at 12 months was 31.6%, and over 70% of all dropouts occurred after the first or second visit [ 22 ].…”
Section: Discussionmentioning
confidence: 99%